2018
DOI: 10.1080/1028415x.2018.1478766
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cognitive function in schizophrenia withN-acetylcysteine: A theoretical review

Abstract: Exploration of how NAC treatment may act to improve cognitive function could guide clinical trials by investigation of the specific neurotransmitter systems and processes involved, allowing for targeted neurological outcome measures. Future research would benefit from the investigation of both in vivo cortical GSH concentration and peripheral plasma GSH in a population of individuals with chronic schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 92 publications
0
30
0
Order By: Relevance
“…N‐acetylcysteine acts as a precursor to glutathione, the primary endogenous antioxidant, neutralizing cellular reactive oxygen and nitrogen. Glutathione production in astrocytes is rate limited by cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…N‐acetylcysteine acts as a precursor to glutathione, the primary endogenous antioxidant, neutralizing cellular reactive oxygen and nitrogen. Glutathione production in astrocytes is rate limited by cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sepehrmanesh et al (2018) [ 69 ] showed that the administration of 1200 mg of NAC had a positive impact on the positive, negative, general, and total psychopathological symptoms analyzed by PANSS, along with an improvement of cognitive performance. A meta-analysis also supported that NAC administered for a period of 24 weeks or more improves the symptoms of schizophrenia, as well as the cognitive domain of working memory, where studies had a daily dose range of 600 mg to 3600 mg [ 70 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Whether NAC has a global impact on cognition based on a general reduction of oxidative stress, versus a more specific action (such as the modulation of N -methyl- d -aspartate [NMDA] receptor pathways) is currently unclear (Yolland et al, 2018). There is some evidence that structures relating to memory and learning are more affected by oxidative stress (Skvarc et al, 2017), and some indication of improvements in specific domains of cognition, depending on the disease process (Hajjar et al, 2018); however, much is still unknown.…”
Section: Introductionmentioning
confidence: 99%